Records of streblidae and nycteribiidae (Diptera) on vespertilionid bats (Chiroptera: Vespertilionidae) from São Paulo State, Brazil - Graciolli, Gustavo; Passos, Fernando C.; Pedro, Wagner A. [UNESP]; Lim, Burton K. (New York Entomological Society, 2002)
New records of five species of batflies (Diptera: Streblidae and Nycteribiidae) on vespertilionid bats are provided from São Paulo State, Brazil.